Sex, honor and citizenship in early Third Republic France - Mansker, Andrea, 1972- (Genders and sexualities in history., 2011)
This book repositions French women's struggle for suffrage within the distinct cultural landscape of the masculine honor system, a system that celebrated male dueling and dictated the proper social and sexual forms of men's comportment prior to the First World War. Whether activists demanded admission to the ritual of the duel or publicly shamed men for their extramarital sexual behavior, they appropriated extralegal honor codes to enact new models of civic participation and to refashion the private politics of the republican family. The book uses unexplored feminist sources, divorce records, parliamentary debates on the name, and evidence of a female "surplus" in France to reorient a body of scholarship that has been limited to masculinity studies. Demonstrating how suffragists deployed an inequitable, prerevolutionary code to construct democratic identities for women, it suggests that modern western feminisms did not derive solely from the French Revolution.